The Frege–Geach Problem, Modus Ponens, and Legal Language - Ogleznev, Vitaly (Problemos, 2018)
[full article, abstract in English; only abstract in Lithuanian]This paper proposes a new pragmatic interpretation of the Frege–Geach problem and presents a possible solution using a model of ascriptive legal language. The first section includes the definition of the Frege–Geach problem. In the second section, I analyze the content of Geach’s critical argument against prescriptivism in ethics. I discuss what Geach means by ascriptivism, why he mixes it with prescriptivism, and why a particular article by Herbert Hart became the subject of criticism by Geach. The third section proposes a possible solution to the Frege–Geach problem based on the explication of the assertoric force of ascriptive legal utterances and the performativity of legal language.
Keywords: ascriptive language, ascriptivism, Frege–Geach Problem, Modus Ponens